2009
DOI: 10.1016/j.molmed.2009.01.002
|View full text |Cite
|
Sign up to set email alerts
|

When apoptosis meets autophagy: deciding cell fate after trauma and sepsis

Abstract: Apoptotic cell death is considered to be an underlying mechanism in immunosuppression and multiple organ dysfunction after trauma–hemorrhage and sepsis. Although studied intensively over the last decade, the role of other cell death mechanisms under similar pathophysiological conditions has remained elusive. Recently, autophagy has emerged as an important mediator of programmed cell death pathways. Here, we review recent advances in our understanding of apoptosis and autophagy and the crosstalk between these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 90 publications
4
87
0
Order By: Relevance
“…5,29,40 However, numerous studies have indicated autophagy suppression at the late stage of the disease. The reduced autophagy activity is associated with organ failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,29,40 However, numerous studies have indicated autophagy suppression at the late stage of the disease. The reduced autophagy activity is associated with organ failure.…”
Section: Discussionmentioning
confidence: 99%
“…39 Autophagy and apoptosis also share common molecular regulators and appear to be antagonistic. 40 To this end, inhibition of autophagy by interferon regulatory factor IRF1 has been shown to activates apoptosis in splenic macrophages. 30 Physiologically, exhaustion of autophagy may result in extrusion of accumulated autophagosomes out of the cells, leading to a proinflammatory response.…”
Section: Kinetics Of Autophagy In Sepsismentioning
confidence: 99%
“…The 'choice' between autophagy and apoptosis may be integral to the fate of cells. The reciprocal regulation between apoptosis and autophagy may affect immune homeostasis in sepsis (28). The induction of autophagy may re-engage or preserve host immune homeostasis, and may avoid the side effects of complete inhibition of apoptosis (28).…”
Section: Clinical Application: Restoration Of Immune Homeostasis By Amentioning
confidence: 99%
“…It has been demonstrated that mitochondria may undergo autophagy, which may be detrimental for the switch between autophagy and apoptosis (28). The term mitophagy is used to refer to mitochondrial degradation by autophagy.…”
Section: Reciprocal Regulation Between Apoptosis and Autophagymentioning
confidence: 99%
See 1 more Smart Citation